Does environmental regulation promote green merger and acquisition? Evidence from the implementation of China’s newly revised Environmental Protection Law - Han, Zhijie; Wang, Yuwei; Pang, Jing (Frontiers in Environmental Science, 2022)
Green merger and acquisition (Green M&A) is one of the ways of corporate environmental investment, which is vital for their green transformation and sustainable development. With the implementation of the newly revised Environmental Protection Law in 2015, this paper investigates the impact of environmental regulation on corporate green M&A using the Differences-in-Differences method with a sample of Chinese listed companies from 2007 to 2020. We found that firms' green M&A increases significantly after the implementation of the new Environmental Protection Law. The promotion effect is more pronounced when the firm is state-owned or faces lower financing constraints. Further analysis reveals that green M&A significantly reduces firms' environmental management costs, enhances green innovation, and has no effect on market performance. This result confirms that after the implementation of the new Environmental Protection Law, companies engage in green M&A for cost and innovation motives rather than market motives.